PENGEMBANGAN SISTEM INFORMASI UNTUK SIMULASI PENILAIAN INSTRUMEN AKREDITASI BERBASIS WEBSITE UNTUK MENGETAHUI KESIAPAN AKREDITASI PRODI - Purwanto, Triyadi Joko; Pertiwi, Yus Andhini Bhekti; Fauza, Gusti; Triyadi, Aan; Roswulandari, Adhianti; Sumiyati, Asri (Jurnal Riset Sistem Informasi dan Teknologi Informasi (JURSISTEKNI), 2025)
Accreditation ensures that the institution meets specific standards for education, student services, management, and various other aspects. Study program accreditation must be carried out every 5 years. Accreditation is a very tiring process that drains energy and time. The problem constantly recurs in every accreditation is the availability of valid and reliable data to fill in the study program performance report (LKPS) spreadsheet, which is the basis for compiling the Self-Evaluation Report (LED). However, after the LED and LKPS are often compiled, the results are not optimal because the maximum value listed in the assessment matrix is ​​not. Accreditation assessment was carried out by evaluating and assessing the implementation of study program learning based on instrument criteria. Because there are so many criteria, dimensions, and indicators, study programs sometimes cannot anticipate the reduction in these points in the assessment. For this reason, a system is needed to assist in assessing study program accreditation so that study programs can simulate the accreditation ranking obtained in real situations. This study aims to build a web application that can assist study programs in simulating accreditation instrument assessments. This study produces software as a web-based information application/system to simulate LED and LKPS assessments in study program accreditation. The nature of the application being built is open, which means that it is highly adaptive and can be used for various accreditation institutions, including if there are changes in their accreditation instruments.